Instructional Media for Autistic Spectrum Disorder (ASD) Children: A Study on Need Analysis - Padmadewi, Ni Nyoman; Artini, Luh Putu; Sindu, I Gede Partha; Shanmuganathan, Thilagavathi; Suarcaya, Putu; Dewi, Kadek Sintya (Journal of Education Reseach and Evaluation, 2023)
ASD children exhibit social functioning issues that indicate difficulty communicating with others and often do not understand why they have to have social interactions with other people. One way of helping them is to develop media based on their needs. This research aimed to analyze the specifications of the media required. The study is designed as a mixed-methods study. The data were collected using a questionnaire in the form of a survey and combined with interviews. The respondents to the survey consisted of 24 respondents from Malaysia, the Netherlands, Canada, and Indonesia, and include teachers from inclusive schools. The selection of the sample used purposive sampling techniques to ensure that they had background knowledge either in education, linguistics, or special education and were willing to be included in the research. The data were analyzed qualitatively and quantitatively. The results of the study show that the media have essential specifications that are: the media should be in the language that supports their learning; the media developed should be able to establish their purpose; the media developed should be able to provide learning support; the media should be in different variations to provide meaningful learning; the media should consider various factors that can affect their ability to access and benefit from different forms of media; the media should be meaningful for assessing students' progress and achievement; and the media should provide various functions. These specifications are the basis for developing the media based on the needs of students with ASD.